2011
DOI: 10.1590/s0066-782x2011005000099
|View full text |Cite
|
Sign up to set email alerts
|

Um novo índice de doppler tecidual para a predição de fibrilação atrial futura em pacientes com insuficiência cardíaca

Abstract: Background: Onset of atrial fibrillation (AF) in patients with heart failure (HF) is usually associated with a high occurrence of cardiovascular complications. E/(E'×S') ratio (E=early diastolic transmitral velocity, E'=early mitral annular diastolic velocity and S'=systolic mitral annulus velocity) has been shown to reflect left ventricular filling pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“… 23 Previous studies demonstrated the usefulness of the E/(e’xs’) ratio to predict new-onset AF and AF recurrence after ECV. 8 , 10 Univariate and multivariate analysis of our data showed that the E/(e’xs’) ratio was a significant predictor of early AF recurrence after ECV and demonstrated higher hazard ratios than E/e’ ratio. ROC analysis revealed that AUCs of E/(e’xs’) and E/e′ ratios were similar: AUC=0.71 and AUC=0.75, respectively.…”
Section: Discussionmentioning
confidence: 72%
“… 23 Previous studies demonstrated the usefulness of the E/(e’xs’) ratio to predict new-onset AF and AF recurrence after ECV. 8 , 10 Univariate and multivariate analysis of our data showed that the E/(e’xs’) ratio was a significant predictor of early AF recurrence after ECV and demonstrated higher hazard ratios than E/e’ ratio. ROC analysis revealed that AUCs of E/(e’xs’) and E/e′ ratios were similar: AUC=0.71 and AUC=0.75, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…[ 7 ] In addition, this parameter resulted useful also in predicting new-onset atrial fibrillation in patients with HF, in sinus rhythm, regardless of EF, and it was the strongest predictor of new-onset AF compared to several other echocardiographic parameters (conventional and TDI parameters), clinical variables, and plasmatic N-terminal pro-B-type natriuretic peptide (NT-pro-BNP) levels. [ 15 ] Recently, the prognostic value of E/(E' × S') average was demonstrated in patients with HF with preserved and reduced EF: the dimensionless index was the only independent predictor of future cardiovascular events (cardiovascular death, nonfatal myocardial infarction, and HF exacerbation) in both HF populations. [ 16 ] According to the theory of the continuous cycle, the present study demonstrates that E/(E' × S') average has a significant prognostic impact also in a population of asymptomatic HF patients.…”
Section: Discussionmentioning
confidence: 99%